ARTIFICIAL INTELLIGENCE BASSED LEARNING INNOVATION FOR ISLAMIC EDUCATION QUALITY - Amalia Ulfa (International Conference on Humanity Education and Society (ICHES), 2026)
The rapid development of artificial intelligence (AI) in the digital era has transformed the learning paradigm in various fields, including Islamic education. AI-based learning innovations are crucial for improving the quality and access of Islamic education. This study aims to examine AI learning innovations in Islamic education, focusing on quality, from three perspectives: opportunities, risks, and implications for equitable distribution of Islamic education. The research method used was a qualitative approach, consisting of a systematic literature review (2023-2025) and thematic analysis. The literature review revealed three main findings. First, AI offers significant opportunities through personalized learning, increased teaching efficiency, and broader and more adaptive access to materials, which can enrich the learning experience of students and educators. Second, there are significant risks, such as gaps in technology access, data privacy issues, and the reduction and potential inconsistency with Islamic values. Third, the implications for equitable distribution of Islamic education are two-fold. AI can support equitable distribution by providing quality learning resources in marginalized areas, but without adequate infrastructure and educator competency, this technology risks widening the gap. In conclusion, the application of AI in Islamic education promises to improve the quality and inclusiveness of learning. However, this requires risk mitigation efforts and supporting policies to ensure this innovation truly supports equitable distribution of the quality of Islamic education.